2001
DOI: 10.1007/s00417-001-0376-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of two intraocular pressure measurement methods: SmartLens dynamic observing tonography versus Goldmann

Abstract: Purpose: To compare intraocular pressure measurements obtained with SmartLens, a gonioscopic contact lens, to those from Goldmann applanation tonometry. Methods: Eighty volunteers (20 healthy individuals and 60 glaucoma patients from the university eye hospital's outpatient department) were examined using conventional Goldmann tonometry and the new SmartLens tool. For each device three replicate measurements were performed. A paired t-test and the corresponding mean difference confidence interval approach were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…They have all been compared with the Goldmann applanation tonometer, which has been considered the gold standard. [1][2][3] When comparing tonometry devices randomisation of methods is necessary because each subsequent measurement lowers the IOP by 0.1-0.4 mm Hg. 4 5 A new tonometry method needs to be accurate and reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…They have all been compared with the Goldmann applanation tonometer, which has been considered the gold standard. [1][2][3] When comparing tonometry devices randomisation of methods is necessary because each subsequent measurement lowers the IOP by 0.1-0.4 mm Hg. 4 5 A new tonometry method needs to be accurate and reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction of the blood flow may cause hypoxia and further cell death and therefore may also initiate diseases like glaucoma and maybe other circulatory problems. In different studies the effect of local glaucoma therapy on ocular hemodynamics is determined using different instruments for IOP- and OPA-measurements [4,6-15]. …”
Section: Introductionmentioning
confidence: 99%
“…2,3 Goldmann believed that as long as the applanated area had a diameter of 3.06 mm (area of 7.354 mm 2 ) normal corneal variations in man did not influence the instrument's reading: 'It does not make any difference if the cornea is more curved or less, or if the eye has a higher or lower rigidity'. 4,5 Since then, however, it has been shown that the tonometer's recordings are affected by a number of normal variations of the globe, such as corneal thickness, 6 corneal curvature, 7 and axial length.…”
Section: Introductionmentioning
confidence: 99%